[tex]\begin{gathered} \text{Given} \\ 3x+4y=7 \\ 4x-2y=24 \\ \text{Multiplying the top equation by 4 gives;} \\ 12x+16y=28\ldots\ldots\text{.}\mathrm{}\text{equation 1} \\ \text{Then to eliminate x, we multiply the bottom equation by -3 and add;} \\ -3(4x-2y)=-3(24) \\ -12x+6y=-72\ldots\ldots\ldots\text{.}\mathrm{}\text{equation }2 \\ \\ by\text{ adding equation 1 to equation 2} \\ 12x+(-12x)+16y+6y=28+(-72)_{} \\ x\text{ is eliminated;} \\ 22y=-44 \\ y=-2 \end{gathered}[/tex]
Hence, the correct option is -3